Latex hemostatic packing as an alternative to damage control surgery: Surgical technique - Pérez Ventura, Segundo Alberto (2019)
The term “damage control surgery” proposed by Rotondo and Schwab in 1993 refers to the rapid initial control of bleeding and contamination, temporary abdominal closure, resuscitation in the ICU, and subsequent reexploring with definitive repair. Based on four cases, we propose a surgical technique with latex hemostatic packing that prevents surgical reexploration. It consists in hemostasis, placing a latex glove filled with 0.9% sodium chloride (latex hemostatic pack) in the area of bleeding and bringing the mouth of the glove through the abdominal wall. Following content evacuation, the glove is removed within 48 to 72 hours.